2007
DOI: 10.1136/ard.2006.063909
|View full text |Cite
|
Sign up to set email alerts
|

Anti- 2GPI-antibody-induced endothelial cell gene expression profiling reveals induction of novel pro-inflammatory genes potentially involved in primary antiphospholipid syndrome

Abstract: Objective: To determine the effects of primary antiphospholipid syndrome (PAPS)-derived anti-b 2 GPI antibodies on gene expression in human umbilical vein endothelial cells (HUVEC) by gene profiling using microarrays. Methods: Anti-b 2 GPI antibodies purified from sera of patients with PAPS or control IgG isolated from normal subjects were incubated with HUVEC for 4 h before isolation of RNA and processing for hybridisation to Affymetrix Human Genome U133A-2.0 arrays. Data were analysed using a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 48 publications
0
23
0
3
Order By: Relevance
“…Several past reports have addressed the activation of human umbilical vein endothelial cells (HUVEC) by a~2GPI (15)(16)(17) and their functional impact which mainly focused on monocyte adhesion (18,19). However, to our current knowledge, none has considered the avidity of the antibodies in relation to any of their cellular effects.…”
Section: Received February 1 2013 -Accepted March 4 2013mentioning
confidence: 99%
See 1 more Smart Citation
“…Several past reports have addressed the activation of human umbilical vein endothelial cells (HUVEC) by a~2GPI (15)(16)(17) and their functional impact which mainly focused on monocyte adhesion (18,19). However, to our current knowledge, none has considered the avidity of the antibodies in relation to any of their cellular effects.…”
Section: Received February 1 2013 -Accepted March 4 2013mentioning
confidence: 99%
“…These reports describe the effects of a~2GPI autoantibodies isolated from patients with APS or monoclonal aPL subpopulations and were conducted mainly on HUVEC. A study by Hamid et al using gene expression microarrays in HUVEC, reported that human polyclonal IgG a~2GPI derived from APS patients induced changes in 115 genes involving apoptosis, coagulation, metabolism, transcription factors/signaling, cytokines/chemokines, adhesion and other molecules, including MCP-1, GRan, IL-8 and IL-6 (17). Several studies observed upregulation ofIL-6 at the protein level by a~2GPI (15,23,24) IgG fractions from patients with APS and~2GPI independent human monoclonal aPL elevated MCP-1 as well as IL-8 production at both mRNA and protein levels in a time-dependent manner in HUVEC (26).…”
Section: Fig 1 Quantificat Ion Of Chemokinelcytokine At the Proteinmentioning
confidence: 99%
“…11 Furthermore, TF was not identified among 101 genes found to be induced in a genomics analysis of anti-b 2 GPI stimulated endothelial cells which are another major source of TF. 26 We hypothesize that this discrepancy between TF gene activation, protein expression and activity may be explained by aPL leading to a cellular re-distribution of intracellular TF to the cell surface as has been shown in monocytes with a high response to LPS. 35 Ultimately, further experiments are required to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of an ankyrin repeat and BTB (POZ) domain containing gene was identified in an earlier genomics analysis of aPL-induced endothelial cell gene expression. 26 Plasminogen activator inhibitor type-1 (PAI-1) is the main inhibitor of urokinase, PAI-2 is predominantly intra-cellular and has a number of anti-inflammatory, anti-proliferative and antiapoptotic functions. 27 Therefore, reduced levels of PAI-2 may allow unopposed action of PAI-1 as found in APS 28 to promote thrombogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss has been correlated with circulating autoantibodies against endothelial cells and their membrane phospholipids [18], such as cardiolipin and β2-glycoprotein 1. These autoantibodies have been shown to activate the inflammatory response of endothelial cells [25,26], which includes breaking tight junctions to facilitate intercellular movement of immune cells [27,28]. Such autoantibody impact on tight junctions of the blood labyrinth barrier is one proposed mechanism for hearing loss by disrupting the sensitive ion homeostatic functions within the stria vascularis.…”
Section: Introductionmentioning
confidence: 99%